2011
DOI: 10.1177/147323001103900327
|View full text |Cite
|
Sign up to set email alerts
|

Association between ABO Blood Groups and Osteoporosis Severity in Chinese Adults Aged 50 Years and over

Abstract: This study investigated whether the ABO blood groups contributed to the severity of osteoporosis in 1452 community-dwelling Chinese adults aged 50 -85 years. Osteoporosis severity was scored as: F 0 , no osteoporosis; F 1 , osteopenia; F 2 , osteoporosis; and F 3 , severe osteoporosis. The proportions of adults with a non-O blood group were 55.0%, 62.0%, 70.8% and 72.6% for the groups with F 0 , F 1 , F 2 and F 3 osteoporosis scores, respectively. Having a non-O blood group was associated with an increased sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…The fact that blood group A was most common in the PKO group of the current study shows consistency with the data of these other two studies. Previous studies in the literature have shown an association between blood group A and disease [17][18][19]. In studies determining the relationship between ABO blood groups and osteoporosis, with the exception of group O, a relationship has been shown with osteoporosis [ 17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that blood group A was most common in the PKO group of the current study shows consistency with the data of these other two studies. Previous studies in the literature have shown an association between blood group A and disease [17][18][19]. In studies determining the relationship between ABO blood groups and osteoporosis, with the exception of group O, a relationship has been shown with osteoporosis [ 17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the literature have shown an association between blood group A and disease [17][18][19]. In studies determining the relationship between ABO blood groups and osteoporosis, with the exception of group O, a relationship has been shown with osteoporosis [ 17,18]. In a study of hip fractures, Buckwalter et al reported increased fracture incidence in the A blood group [19].…”
Section: Discussionmentioning
confidence: 99%
“…11 Two research groups have independently identified elderly non-O individuals as having an increased incidence and severity of osteoporosis compared with those of blood group O. 12,13 In their study, Choi and Pai found patients with the blood group AB to have the highest frequency of osteoporosis and the lowest bone mineral density. 13 Lourie et al reported group A individuals to be overrepresented in patients with osteoporosis compared with a cohort of blood donors.…”
Section: Discussionmentioning
confidence: 99%
“…This encourages the hypothesis that some G3S are eQTL that may modulate gene expression in the adrenal gland, with gene function dependent on the level of sex hormones. This was also an intriguing finding given that ABO blood groups have been known to associate with osteoporosis and osteoporosis severity (Choi and Pai 2004;Lu and Li 2011). For WHR, we detected previously known, large-magnitude G3S interactions that were discovered using WHR or WHRadjBMI (Heid et al 2010;Randall et al 2013;Shungin et al 2015;Winkler et al 2015), but additionally discovered novel, small magnitude G3S interactions near such genes as ESR1 and ABCA1.…”
Section: Discussionmentioning
confidence: 63%